Freedom to Learn or Freedom to Learn?A Critical Review of the Implementation of the Independent Curriculum in the 3T Regions - Amalia Tasya (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the implementation of the Independent Curriculum in 3T (Disadvantaged, Frontier, and Outermost) regions, focusing on the challenges, opportunities, and impacts faced in the context of specific local needs. The Independent Curriculum, introduced in 2021, aims to give educational institutions autonomy in developing curricula tailored to student needs and local contexts. Despite its significant potential for improving the quality of education, the implementation of the Independent Curriculum in 3T regions faces various obstacles, including limited infrastructure, limited access to technology, and a shortage of trained teaching staff. This study used qualitative methods with a descriptive analytical approach, involving in-depth interviews, observations, and documentation studies in two 3T regions: North Lombok Regency and Mahakam Hulu Regency. The results show that although project-based learning and the concept of